Barrier properties and structure of liquid crystalline epoxy and its nanocomposites. (25th April 2018) - Rao, YuanQiao; Liu, Andong; O'Connell, Kathleen
Abstract: There is ever increasing demand for a suitable sealant material to protect electronic devices, in particular, different displays. We present a new approach to generate a liquid processible material that possesses excellent barrier properties and flexibility that can be used for electronic encapsulation. The liquid processable material is based on liquid crystalline (LC) epoxy diglycidyl ether of 4, 4′-dihydroxy-α-methylstilbene (DGE-DHAMS or EDHAMS) and its nanocomposite comprising organo-modified montmorillonite clay. The best-achieved water vapor transmission rate is 4.5 g-mil/m 2 -day at ambient pressure, which is more than 20 times better than that of a conventional bisphenol A epoxy. The improved barrier performance comes from the reduction in the water diffusivity. The diffusivity in the liquid crystalline epoxy is 1.25 × 10 −9 cm 2 /s, one order of magnitude lower than that of bisphenol A epoxy. The addition of 1 vol% of organoclay further reduces the diffusivity by 2 times. The cavity size of the free volume of the liquid crystalline epoxy is much smaller than that of conventional bisphenol A epoxy as measured by positron annihilation lifetime spectroscopy, suggesting that the improved barrier property originates from this reduced free volume cavity size. The free volume cavity size of the film with an addition of 1 vol% of an organically modified montmorillonite clay is similar to that of the liquid crystalline epoxy. We hypothesize that the additional barrier performance improvement by the nanoclay is due to its effect on the liquid crystalline phase morphology (reduced LC phase domain sizes) or the tortuosity effect of the high aspect ratio particles. The material also has excellent adhesion, optical transparency, and thermal stability. Graphical abstract: Image 1 Highlights: LC epoxy and its nanoclay composites have good water vapor barrier properties. LC epoxy and its nanocomposites are flexible and optically transparent. The barrier property improvement is due to reduced diffusivity. The barrier properties originate from the reduced free volume cavity size and fraction. Nanoclay serves as a nucleator for LC epoxy and provides tortuosity for transport.